Penguasaan Bahasa Arab Pada Anak Down Syndrome dalam Faktor Neurologis - Laili Mas Ulliyah Hasan Laili; Siti Durotun Naseha; Firdausi Nurharini (Program Studi Pendidikan Bahasa Arab Universitas Nahdlatul Ulama Purwokerto, 2023)
The purpose of this study was to explain the characteristics of children who experience neurological barriers that explain the phonetic and phonemic mastery of the Arabic second language in children with Down syndrome disorders, and explain the phonetic mastery of Arabic second language phonetics in children with Down syndrome disorders. Neurological factors were evaluated in this study through descriptive qualitative methods. To obtain relevant data in this study, researchers conducted an interview with one of the Down syndrome children at Down Syndrome School (DSS) Surabaya, who used dimensional sound symbols in Arabic. The study found that traits of children with Down syndrome in DSS Surabaya include cognitive developmental delays, language disorders, and motor problems. Imperfections in the nerve centers are the cause of this habit. Phonetic studies looked at mastery of the second language of Arabic in children with Down syndrome including consonant sounds and sound producers; Phonemic research includes sound replacement, vowel modification, gemination (lightening of pronunciation), and dissimilation (differentiation).